Bright features in the solar photosphere - Kostik, R.I.; Khomenko, E.V. (Кинематика и физика небесных тел, 2005)
We report thermodynamical properties of so-called “thermal plume” observed near the solar disc centre in 2001. The spectral observations of two iron lines analysed were obtained with the use of the Vacuum Tower Telescope (Tenerife).